Logical diagnosis model turbojet engine including double-circuit intermittent flow of his injuries - Стьопушкіна, О.П.; Попов, О.В.; Корсуненко, М.В.; Слєпухіна, І.А. (Proceedings of National Aviation University (archive), 2007)
In this article is considered question of the change quantitative and qualitative factors of the technical condition constructive element running part of jet engine. As a result called on experimental studies diagnostic sign were definite sign with provision for intermittent damages and on base this is built expert model of the turbojet double-circuit engine.